CHARACTERIZATION OF NOVEL FACTORS REGULATING ENDOTHELIAL BARRIER DURING METASTASIS - Kaipainen, Pihla (My University, 2024)
Progressive, metastatic cancer is a leading cause of cancer-related deaths worldwide. One of the critical steps of the metastatic cascade is the colonization of circulating tumor cells in the distant tissues, where cancer cells cross the blood vessel wall to initiate metastatic growth in the distant organs. Vascular endothelium acts as a gatekeeper between circulating tumor cells and metastatic organs. However, the role of endothelial cells in the regulation of cancer cell fate in the metastatic niche is poorly understood. Here, we show that endothelial Pim-3 kinase regulates the endothelial barrier integrity during early steps of cancer cell colonization of the lungs. Single cell mRNA sequencing of the metastatic B16-F10 murine melanoma model revealed that Pim3 was upregulated in the lung endothelial cells six hours after arrival of the melanoma cells in the lungs. Upregulation of Pim3 was further validated in spontaneous metastasis models. Further studies showed that administration of a pan-Pim kinase inhibitor AZD-1208 in mice increased melanoma metastasis and leakage in the murine lungs. In cultured human endothelial cells AZD1208 decreased Cadherin 5 based cell-cell junctions and increased endothelial cell permeability in an electrical cell impedance sensing assay. Similar Cadherin 5 reduction was seen in PIM3 silenced endothelial cells. Pim3 is a well-known oncogene and Pim inhibitors have been investigated as cancer therapies in recent years. However, the inhibitors did not provide the expected outcomes, and currently clinical trials have been attired. Therefore, whereas targeting Pim kinases is known to decrease tumor cell survival, results from this work suggest that Pim inhibitors may simultaneously weaken the vascular barrier. Thus, the results presented in this thesis reveal a potential mechanism behind unsuccessful Pim inhibitor cancer trials. Notably, the results also call for a better understanding of the effects of cancer therapies on the host cells of the tumor microenvironment.
Keywords: Pim3, metastasis, endothelial cells, Cadherin 5